AN ANALYSIS OF TEACHER’S QUESTIONING STRATEGIES AND STUDENTS’ RESPONSES IN ENGLISH CLASSROOM INTERACTION - Aninatul Mukharomah; Taslimah Retno Marpinjun; Ika Rakhmawati (STKIP PGRI Trenggalek, 2018)
This research was aimed to know the strategies of question used by the teacher and also to know students’ response to the questions given by the teacher in English classroom interaction. This research was used qualitative research design concerning with descriptive qualitative method. The subjects of this research were the teacher and 66 of eight grade students of SMPN 1 Trenggalek. The study was done by observing and taking video recordings. Observation field note and questionnaire were also used as the instruments to gather the data. Based on the findings of instruments above, the researcher found seven points of teacher’s questioning strategies such teacher used some types of question in questioning the students, the teacher was questioning the students in all session of teaching, the teacher used wait time when she was questioning the students, and vice versa. The second research findings were students' responses that showed the most responses were in the target language form applied with chorus responses. The result of this research can be applied by students to response teacher’s question as a way to get more active to join the classroom activities. It is also suggested to the teachers to develop their teaching strategies, so, the students could gain the best learning process.